REFlex: rule engine for flexible processes - Silva, Natália Cabral (2014)
Declarative business process modeling is a flexible approach to business process management in which participants can decide the order in which activities are performed. Business rules are employed to determine restrictions and obligations that must be satisfied during execution time. Such business rules describe what must or must not be done during the process execution, but do not prescribe how. In this way, complex control-flows are simplified and participants have more flexibility to handle unpredicted situations. The methods and tools currently available to model and execute declarative processes present several limitations that impair their use to this application. In particular, the well-known approach that employs Linear Temporal Logic (LTL) has the drawback of the state space explosion as the size of the process model grows. Although approaches proposing memory efficient methods have been proposed in the literature, they are not able to properly guarantee the correct termination of the process, since they allow the user to reach deadlock states. Moreover, current implementations of declarative business process engines focus only on manual activities. Automatic communication with external applications to exchange data and reuse functionality is barely supported. Such automation opportunities could be better exploited by a declarative engine that integrates with existing SOC technologies. This work proposes a novel graph-based rule engine called REFlex that does not share the problems presented by other engines, being better suited to model declarative business processes than the techniques currently in use. Additionally, such engine fills this gap between declarative processes and SOC. The REFlex orchestrator is an efficient, data-aware declarative web services orchestrator. It enables participants to call external web services to perform automated tasks. Different from related work, the REFlex algorithm does not depend on the generation of all reachable states, which makes it well suited to model large and complex business processes. Moreover, REFlex is capable of modeling data-dependent business rules, which provides unprecedented context awareness and modeling power to the declarative paradigm.